Anti-nociceptive and Antipyretic Activities of Hydroalcoholic Extract of Cassia sophera Linn. Leaves - Roy, Debasish; Shill, Manik Chandra; Dev, Shrabanti; Deb, Debashish; Shahriar, Masum; Das, Asish Kumar; Choudhuri, M Shahabuddin Kabir (Bangladesh Pharmaceutical Journal, 2012)
The crude hydroalcoholic extract of Cassia sophera Linn. leaves were investigated for its possible analgesic and antipyretic activities in rodents. The peripheral analgesic activity of C. sophera leaves was studied using acetic acidinduced writhing in mice and central analgesic activity was evaluated by using heat-induced pain in mice. The antipyretic activity of HECS was studied in Brewers yeast-induced pyrexia in rats. All these experiments were done at the doses of 300 and 600 mg/kg body weight. Intraperitoneal administration of C. sophera hydroalcoholic extract (HECS) produced significant (P<0.01) reduction in number of writhing induced by acetic-acid. Moreover, in hotplate test, HECS significantly (P<0.01) raised the pain threshold at different time of observation (0-180 min) in comparison with control. The extract also showed significant as well as dose-dependent antipyretic activity in Brewers yeast-induced pyrexia in rats throughout the observation period of 4 h. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12573 Bangladesh Pharmaceutical Journal 15(2): 107-111, 2012